2018
DOI: 10.1097/md.0000000000013368
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use of single-port surgery in the conservative management of hepatic portal vein gas

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…CT scans are highly-sensitive tools for detecting PVG and PI [3,4,7,28]. Moreover, contrast-enhanced CT imaging is a useful investigative tool for identifying the underlying disease, especially bowel ischemia and gastrointestinal perforation [18,28,29]. We assessed representative CT ndings of acute abdominal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT scans are highly-sensitive tools for detecting PVG and PI [3,4,7,28]. Moreover, contrast-enhanced CT imaging is a useful investigative tool for identifying the underlying disease, especially bowel ischemia and gastrointestinal perforation [18,28,29]. We assessed representative CT ndings of acute abdominal disease.…”
Section: Discussionmentioning
confidence: 99%
“…2). Some authors also reported that wide spread PVG was correlated with poor prognosis [5,13,17,29]. From a pathophysiological standpoint, wide spread PVG often indicates progressive mucosal damage and can re ect the severity of the patient's condition [32].…”
Section: Discussionmentioning
confidence: 99%